An international multilevel competition policy system - Oliver Budzinski (Universität Duisburg-Essen, Fachbereich Wirtschaftswissenschaften, 2007)
This paper develops a proposal for an international multilevel competition policy system, which draws on the insights of the analysis of multilevel systems of institutions. In doing so, it targets to contribute to bridge a gap in the current world economic order, i.e. the supranational governance of private international restrictions to market competition. Such a governance can effectively be designed against the background of a combination of the well-known nondiscrimination principle and a lead jurisdiction model. Put very briefly, competition policy on the global level restricts itself to the selection and appointment of appropriate lead jurisdictions for concrete cross-border antitrust cases, while the substantive treatment remains within the competence of the existing national and regional-supranational antitrust regimes.
Keywords: F02; K21; L40; F53; 330; international competition policy; multilevel systems; international governance; economics of federalism; international economic order; international antitrust; Wettbewerbspolitik; Internationale wirtschaftspolitische Koordination; Internationales Wettbewerbsrecht; Organisation; Theorie